Rational design, synthesis and testing of novel tricyclic topoisomerase inhibitors for the treatment of bacterial infections part 2. Issue 12 (18th September 2020) - Kirk, R.; Ratcliffe, A.; Noonan, G.; Uosis-Martin, M.; Lyth, D.; Bardell-Cox, O.; Massam, J.; Schofield, P.; Lyons, A.; Clare, D.; Maclean, J.; Smith, A.; et al.
Abstract : We disclose the discovery of REDX07965, a novel tricyclic topoisomerase inhibitor (NTTI) which has broad spectrum activity, favourable in vitro pharmacokinetic properties and selectivity versus human topoisomerase II. Abstract : Building on our previously-reported novel tricyclic topoisomerase inhibitors (NTTIs), we disclose the discovery of REDX07965, which has an MIC90 of 0.5 μg mL −1 against Staphylococcus aureus, favourable in vitro pharmacokinetic properties, selectivity versus human topoisomerase II and an acceptable toxicity profile. The results herein validate a rational design approach to address the urgent unmet medical need for novel antibiotics.